CHANGES OF AMMONIA, NITRITE, AND NITRATE CONCENTRATION IN SHRIMP AQUACULTURE WASTEWATER WITH NANOTECHNOLOGY - Chandra, William
Aquaculture is the cultivation of marine biota. Wastewater from aquaculture usually contains nutrients in high concentration that can pollute the environment. Micro-nanobubbles can be used to treat the wastewater resulted from vannamei shrimp aquaculture. This study aims to assess the rate of change of the concentration of ammonia, nitrite and nitrate pollutants in used aquaculture water with micro-nanobubble technology. Water sample is acquired from shrimp aquaculture pool in Block I1 in BLUPPB Karawang. There are 3 systems with the volume of 60L each with different treatments, the first system is not given any treatment (System A), the second system is aerated with ordinary air micro-nanobubbles (System B), and the third system is aerated with ozone micro-nanobubbles (System C). The collected data consists of temperature, pH, salinity, dissolved oxygen, and total dissolved solids which are measured by Lutron-WA2017SD. The concentration of ammonia, nitrite, and nitrate is determined by spectrophotometry. The data collection is conducted every 12 hours for 1 week starting from 25/06/2019 – 02/07/2019. The use of ordinary air and ozone micro-nanobubbles generator can reduce ammonia concentrations, but increase nitrate concentrations in system B and C. In system B, ammonia levels is reduced at the rate of -0.009 mg/L/day and nitrate is increased at the rate of 0.011 mg/L/day. In system C, ammonia is reduced at the rate of -0.0078 mg/L/day and nitrate is increased at the rate of 0.0156 mg/L/day. The highest average rate of changes in concentration per day is 0.0156 mg/L/day for nitrate in system C, and the lowest is 0 mg/L/day for nitrite and nitrate in system A and nitrite in system C. Ammonia’s maintenance and effluent quality standards are met at 72nd hour for system B, and 144th hour for system C. Nitrite’s maintenance and effluent quality standards are always met by system A and C because nitrite formation does not occur, however system B exceeds nitrite maintenance quality standards at 108th hour, but always meet effluent quality standards for nitrite. System B and C exceeds the maintenance quality standard at 60th and 12th hour, but always meet the nitrate effluent quality standard.